2013
DOI: 10.1111/acer.12057
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Tolerance of Voltage‐Gated Calcium Channels is Evident After Short Exposures to Alcohol in Vasopressin‐Releasing Nerve Terminals

Abstract: These data indicate that a brief alcohol exposure affects subsequent alcohol sensitivity of VGCCs and neuropeptide release from presynaptic terminals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…Therefore, it is possible that voltage-gated Ca 2+ channel function is inhibited while ethanol is present and fully recovers during withdrawal. Indeed, rapid development of tolerance of L-type voltage-gated Ca 2+ channels to ethanol has been documented in neurohypophysial terminals (Pietrzykowski et al, 2013). Moreover, the pups were older at the time of slice collection in the present study (P6-8 and 13-15) vs. our previous study (P4-6), suggesting that the effect of ethanol on voltage-gated Ca 2+ channels is age-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that voltage-gated Ca 2+ channel function is inhibited while ethanol is present and fully recovers during withdrawal. Indeed, rapid development of tolerance of L-type voltage-gated Ca 2+ channels to ethanol has been documented in neurohypophysial terminals (Pietrzykowski et al, 2013). Moreover, the pups were older at the time of slice collection in the present study (P6-8 and 13-15) vs. our previous study (P4-6), suggesting that the effect of ethanol on voltage-gated Ca 2+ channels is age-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implicated voltage-gated calcium channels in several alcohol-related behaviors, including alcohol consumption and withdrawal syndrome (Newton et al, 2004; Varodayan et al, 2017b; Walter and Messing, 1999; Watson and Little, 2002). Multiple groups have also reported that alcohol both inhibits (Belia et al, 1995; Maldve et al, 2004; Mullikin-Kilpatrick and Treistman, 1993; Pietrzykowski et al, 2013; Xiao et al, 2005; Zucca and Valenzuela, 2010) and enhances (Belia et al, 1995; Pietrzykowski et al, 2013; Simasko et al, 1999) voltage-gated calcium channel activity, and alcohol’s actions on voltage-gated calcium channels regulate GABA release in several brain regions (Hirono et al, 2009; Varodayan et al, 2017b; Zucca and Valenzuela, 2010). Similarly, the CRF system can inhibit (Tao et al, 2008, 2009, 2006) or enhance (Yu and Shinnick-Gallagher, 1998) voltage-gated calcium channel activity to modulate CeA synaptic transmission (Krishnan et al, 2010; Pollandt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Reprinted with permission (Pietrzykowski et al, 2013). In particular, scaffolding ance in BK and voltage-gated calcium channels.…”
Section: Scaffolding/cytoskeletal Protein Interactions Regulating Chamentioning
confidence: 99%
“…A recent study from our laboratory has examined acute tolerance to alcohol in voltage-gated calcium channels (VGCCs) recorded in rat neurohypophysial terminals (i.e., within the posterior pituitary), allowing comparison with previous results obtained in this preparation for BK channels (Pietrzykowski et al, 2004;Pietrzykowski et al, 2013). Thus it was possible to compare the temporal characteristics of molecular tolerance for two different channel proteins within the same cellular membrane (although possibly different microdomains within that membrane).…”
Section: Molecular Tolerance Of Voltage-gated Calcium Channels Is Coomentioning
confidence: 99%
See 1 more Smart Citation